Ambivalensi Kebijakan Pertambangan Rakyat dalam Perspektif Etika Islam dan Maqasid al-Syari‘ah - Gusti Andrie Asriansyah; Dwi Surya Atmaja (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the ambivalence of artisanal mining policies in Landak Regency from the perspective of Islamic ethics and maqasid al-syari'ah. Using a qualitative approach with case studies in Meranti and Kuala Behe sub-districts, this research analyzes the gap between state regulations (2025 Minerba Law), the meaning of rizq (sustenance) among Muslim miners, local philanthropic practices (HUMUS), and ecological awareness. The findings indicate that: (1) miners interpret rizq ambivalently as Allah's blessing requiring effort, yet facing legal dilemmas and ecological impacts; (2) HUMUS functions as a mechanism for moral legitimacy and social solidarity, but potentially becomes spiritual compensation for environmental damage; (3) ecological awareness exists in an ambivalent position between moral recognition and structural inability to change; (4) the 2025 Minerba Law places artisanal miners in a marginal position, though the People's Mining Area (WPR) policy offers a middle ground. From the maqasid al-syari'ah perspective, conflicts between hifz al-mal (protection of wealth), hifz al-nafs (protection of life), and hifz al-bi'ah (protection of environment) require structural solutions based on ecological justice and Islamic economics, particularly through a musyarakah-based mining cooperative model